Uma análise da construção do pensamento científico do conceito de ditadura militar proposta em livros didáticos de história do ensino fundamental - Covre, Ariane Lia (2022)
From the questioning about how the themes related to the period of the Military Dictatorship are developed in the schools, this research had as main objective to investigate how the scientific thinking of the concept of the Military Dictatorship can be developed with the contribution of the textbooks. We start from the hypothesis that conceptual learning on the theme of the Military Dictatorship can promote the development of scientific concepts about this period, allowing students to problematize and critically analyse. The specific objectives of this work were: to select the central elements for the development of scientific thought available in the literature on cultural-historical theory; to relate aspects of historiography on the theme of the Military Dictatorship to the overview of the approach to the concept carried out by History textbooks, describe the understanding of the concept of Military Dictatorship through the investigation of conceptual links and analyze the way in which the construction of the concept of Military Dictatorship in Two History Textbooks of the 9th Year of Elementary School. The criterion for choosing the two textbooks analyzed was based on the scope of this didactic resource in the teaching and learning process and because they are among the most chosen books by the schools that participated in the PNLD for four consecutive years. Based on historical-cultural theory to understand the sociocultural, historical, and philosophical aspects that configure scientific thinking and conceptual learning of the concept of Military Dictatorship, we describe the elements that enable the construction of scientific thinking about Military Dictatorship according to conceptual, internal and external links , present in the organization of the teaching of the selected books. We assume as a theoretical-methodological reference the content analysis proposed by Bardin. The analysis model was based on the a priori choice of conceptual links, authoritarianism and democratic rupture, to identify the way in which the selected History textbooks present the concept of Military Dictatorship. We conclude that the logic of organizing the content of textbooks, in general, still presents problems related to the traditional perspective of History teaching on the theme of the Military Dictatorship. Elements such as the opportunity for problematization, the perspective of exploring conflicts in a continuous and related way and the presence of different social groups in the constitution of historical processes, are provided, but in considerably different ways in the two analyzed books. In this way, textbooks present advances in the sense of contributing to the development of the conceptual nexus of Military Dictatorship. However, this contribution is not predominant in the sense of guaranteeing scientific understanding of this period that overcomes the interpretations crystallized in memory and common sense.